Determination of free steroidal compounds in vegetable oils by comprehensive two-dimensional gas chromatography coupled to time-of-flight mass spectrometry. (15th April 2018) - Xu, Baocheng; Zhang, Liangxiao; Ma, Fei; Zhang, Wen; Wang, Xiupin; Zhang, Qi; Luo, Denglin; Ma, Hongyan; Li, Peiwu
Graphical abstract: Highlights: A novel GC × GC-TOF/MS method was developed for analyzing 31 steroidal compounds. The method could provide better separation and higher sensitivity compared to 1D GC. Thirty-one steroidal compounds were completely separated and determined. The distributions of free steroidal compounds in 5 types of oils were also analyzed. Abstract: A method based on comprehensive two-dimensional gas chromatography coupled to time-of-flight mass spectrometry (GC × GC-TOF/MS) was developed to analyze steroidal compounds in vegetable oils, which could provide better separation and higher sensitivity than conventional one dimensional gas chromatography, and allowed determination of 31 sterols and triterpene alcohols in one injection. Furthermore, the approach also permitted separation and detection of small amounts of other compounds (may be steroidal compounds whose molecular structures have not been confirmed), which were obscured in the lower-resolution single-column technique. With the help of the GC × GC system, a more elaborate and complete information regarding the distributions and concentrations of free phytosterols and triterpene alcohols in safflower seed oil, soybean oil, rapeseed oil, sunflower seed oil and peanut oil were obtained. The proposed method could potentially open a new opportunity for the more in-depth knowledge of the steroidal compounds of vegetable oils.